Application Of Perineum Wound Healing With Binahong Leaf Boiled Water And Fishcork Extract - Indrayani, Eni; Indriyastuti, Hastin Ika; Lestari, Medzelia Efenti (Prosiding University Research Colloquium, 2022)
Background: Postpartum mothers usually have perineal wound. Perineal wound is perineal tear during delivery process. It occurs in almost all first deliveries and also many happen to subsequent deliveries. To hande (or to heal) perineal wound, it can be done by applying binahong leaf boiled water and fishcork extract. Objective: To determine the acceleration of the perineal wound healing of postpartum mothers by using binahong leaf boiled water and fishcork extract.. Method: This research is a qualitative descriptive with a case-study approach.The participants were 24 postpartum mothers who met the inclusion criteria. The instruments used were observation sheets, reeda scala sheets and a camera. The data were obtained through interview, observation, and documentation. Results: after being given boiled water from binahong leaves and snakehead fish extract for 7 days to 24 participants, 20 people (83.3%) healed on day 6 and 4 people (16.7%) healed on day 7. Wound healing time an average of 6.15 days has experienced faster unification. The effectiveness of boiled water from binahong leaves on the healing of perineal rupture in 24 respondents showed that 83.3% of perineal rupture healed in the fast category (< 6 days). Conclusion: The application of boiled water of binahong leaf and extract of fishcork can help postpartum mothers heal their perineal wounds.